Countermeasures to Prescription and over-the-Counter Drug-Impaired Driving: Pharmacy & Medical and Education & Advertising. (June 2018) - Camden, Matthew; Smith, Ryan; Turturici, Marissa; Arnold, Lindsay; Kelley-Baker, Tara
2 nd Highest Scoring Abstract: Researcher : Background: Despite the prevalence of prescription and over-the-counter (OTC) drug use, many individuals are unaware that some medications are potentially driver impairing. Current countermeasures to reduce drugged driving often focus on law enforcement. However, law enforcement alone is likely insufficient to prevent prescription- and OTC-drug-impaired driving. Because the pharmacy and medical communities are the primary providers of patient counseling concerning prescription and OTC drugs, they may be uniquely positioned to reduce prescription- and OTC-drug-impaired driving. Furthermore, education and advertising targeted to both practitioners and consumers may help increase knowledge about the risks and effects of potentially impairing prescription and OTC drugs. Methods: This project used a systematic literature review, an expert roundtable, and expert interviews to identify pharmacy/medical and education/advertising countermeasures to reduce prescription- and OTC-drug-impaired driving. This approach allowed recommendations to be informed by both empirical research and expert insights to arrive at a comprehensive report containing both evidence-based approaches and expert perspectives on countermeasures to impaired driving by prescription and OTC drugs. Results: Nineteen countermeasures were identified as pharmacological or medical practices to reduce prescription- and OTC-drug-impaired driving. These countermeasures were grouped into three categories: patient counseling, reducing and restricting the prescribing of impairing medications, and prescription labelling. Countermeasures involving patient counseling either aim to increase its use for impairing medications or to regulate the way in which it is presented. The second group of countermeasures focused on reducing the number of potentially impairing drugs that are prescribed and used. The last group of countermeasures focused on improving prescription labels to make warnings more noticeable and to increase compliance with driving-related warnings. Fourteen countermeasures were identified as educational or advertising opportunities to reduce prescription- and OTC-drug-impaired driving. These countermeasures not only target drivers, but also individuals who interact with drivers and those who affect the outcomes of impaired-driving cases. Overall, the education and advertising countermeasure recommendations vary widely. Conclusions: In general, many of the countermeasures related to pharmacy/medical and education/advertising were identified as the direct result of the expert roundtable and interviews. Although there are numerous opportunities in the pharmacy/medical profession and through education/advertising to reduce prescription- and OTC-drug-impaired driving, very few countermeasures have been empirically tested. This presentation will include an interactive activity targeting misconceptions on this topic and highlight key research findings. It is also one component of a session regarding countermeasures to prescription- and OTC-drug-impaired driving.